Cardioneuroablation for successful treatment of symptomatic bradycardia in a 12-year-old child after a 6-month follow-up - Xu, Xin; He, Shuang; Liu, Qian; Liu, Ruixi; Zhang, Lei; Chen, Weijie; Yin, Yuehui; Lu, Tiewei (Frontiers in Cardiovascular Medicine, 2023)
Background Cardioneuroablation (CNA) is recognized as a promising therapeutic option for adults with severe symptomatic bradycardia caused by excessive vagal tone. However, no pediatric cases have been reported to date. Therefore, the aim of this study is to evaluate the feasibility and efficacy of CNA in children. Methods A 12-year-old male patient was hospitalized with symptoms of fatigue, palpitations, and syncope for more than 2 months, and was definitively diagnosed with functional sinoatrial node dysfunction by using a 12-lead electrocardiogram, 24-h Holter monitoring, loading dose of atropine test (0.04 mg/kg), and treadmill exercise test. Simultaneously, whole-exome sequencing was performed on the child and his core family members. After completing the preoperative examination and signing the informed consent form, the child underwent CNA therapy. Results First, the electroanatomic structures of both atria were mapped out by using the Carto 3 system, according to the protocol of purely anatomy-guided and local fractionated intracardiac electrogram–guided CNA methods. Then, the local fractionated intracardiac electrograms of each cardiac ganglionated plexus (GP), including the GP between the aortic root and the medial wall of the superior vena cava, the GP between the posterior wall of the coronary sinus ostium and the left atrium, the GP between the anterior antrum of the right superior pulmonary vein and the superior vena cava, the GP in the superolateral area around the root of the left superior pulmonary vein, the GP around the root of the right inferior pulmonary vein, and the GP around the root of the left inferior pulmonary vein, were used as targets for ablation at a power of 30 W with an ablation index of 350–400. At a 6-month follow-up, the child's heart rhythm saw a complete restoration to sinus rhythm and clinical symptoms disappeared. Conclusion The first application of CNA in a child with symptomatic sinus bradycardia was achieved with better clinical outcomes. CNA can be carried out cautiously in children under suitable indications.